The Effect of the Supernatant of Phytohemagglutinin (PHA) Stimulated Lymphocytes on the Isolated Rat Heart - S Niazmand; N Zabihi; F Harandizadeh,; AR Rezaee (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2011)
BACKGROUND AND OBJECTIVE: Cytokines are mainly released during immune responses to antigens. In some circumstances such as toxic shock during super-antigen stimulation, high level of cytokines are released which it may have a dramatic impact on cardiovascular system. Therefore, in the present study the effects of supernatant of Phytohemaglotinin (PHA)- stimulated lymphocytes on isolated heart in rat have been evaluated.METHODS: This is an interventional study which was arranged on 20 male Wistar rats weighed 200-250g. The animals were randomly divided in two groups of control and test. The isolated heart in control group received the cell culture medium with PHA, while in test group the supernatants of PHA stimulated lymphocytes were introduced to isolated hearts. Three dilutions of supernatants (1/800, 1/400 and 1/200) on isolated rat hearts were used. Each concentration was infused to the heart for 10 minutes and the heart rate and the intraventricular pressure were recorded for 40 minutes. The peripheral blood mononuclear cells from healthy volunteers were isolated and stimulated by PHA in vitro for three days and then the supernatants were harvested. FINDINGS: The highest dilution, 1/800, reduced the heart rate 1 and 2 minute after infusion significantly (p<0.05). This effect was significant 10 minutes after infusion for 1/400 and 1/200 dilutions as well. However, the effect of supernatant on the Max dp/dt, Min dp/dt, Max LV and Min LV were not significant.CONCLUSION: In general the data in the present study shows that cytokine pattern of PHA stimulated lymphocyte had a marked negative impact on heart rate which might be due to the effect of these cytokines on stimulatory and conductivity (chronotropy) of cardiac muscle. On the other hand, there was not any significant effect on contractility.